Facts about Flavonoids - Inbar Schapsis; Wendy J. Dahl (EDIS)
Flavonoids are organic compounds that occur naturally in plants. More than five thousand flavonoid compounds exist in nature, but those found in foods fall into six major categories: flavonols, anthocyanidins, isoflavones, flavan-3-ols, flavones, and flavonones. The compounds in these categories are of interest because of their potential health benefits. This 4-page fact sheet was written by Inbar Schapsis and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, February 2014.